ḤADĪTH AND THE COVID-19 PANDEMIC: PRACTICE OF ISLAMIC STUDIES CIRCLE AT PESANTREN DARUS-SUNNAH, SOUTH TANGERANG - Imam Subchi; M. Anwar Syarifuddin; Ilham Fikri Ma'arif (Peminat Ilmu Ushuluddin, 2021)
This study discusses how the Ḥadīth related to the pandemic and how the practice of a ḥadīth boarding school - Darus-Sunnah in South Tangerang, Banten, Indonesia- deal with this issue using a qualitative, and descriptive-analytical method with an anthropological-phenomenological paradigm, this research identifies and constructs their discussion on pandemic and their effort to deal with it. The study finds that Darus-Sunnah bases their discussion about the Covid-19 outbreak on Ḥadīth sources. It also finds that understanding the Prophet’s traditions can thoroughly help to prevent the spread of Covid-19 as the Ḥadīth sources suggest to avoid the possibility for the viruses to transmit to others, and recommend to collaborate between religious, government, and health care agents in combatting the pandemic.